Ocena trafności prognoz upadłości przedsiębiorstw wyznaczonych na podstawie funkcji dyskryminacyjnych - Rólczyński, Tomasz (The Estimate of the Forecast Rightness of Companies Bankruptcy Built on Discriminatory Functions, 2006)
Discriminatory functions apply to forecasting companies bankruptcy. In order to be effective instrument to build forecast it is necessary to estimate parameters of model, mirrors the realities of companies functioning. For polish conditions this functions were created by D. Hadasik, I. Gajdka and D. Stos, A. Hołda. In this paper models were verified which were build for polish economy. It was checked if they still posses predictable values and had the possibility to predict bankruptcy independently of the branch and forms of company's property
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2006; nr 1112, s. 286-294